Perancangan dan Pembuatan Video Company Profile PT. Batam Indonesia Gemilang - Tony Wibowo; Jerremy Alexander (Conference on Business, Social Sciences and Technology (CoNeScINTech), 2021)
A Limited Liability Company (or abbreviated as Ltd.) is run by the company's organs, namely the General Meeting of Shareholders, Directors and Board of Commissioners jointly. Ltd. itself is a capital partnership. The problems obtained in this research; Batam Indonesia Gemilang Ltd. needs a company profile video to provide any information to all consumers. There’s a purpose for this research, which is to help the business of Batam Indonesia Gemilang Ltd. in conducting promotions and providing all informations to the public, which is all about Batam Indonesia Gemilang Ltd. The research method used is Data Collection Techniques, this method contains stages such as observation, interviews, and literature study. This research result of a company profile video will be implemented into social media YouTube